Factors that Affect the Success of Students with Emotional and Behavioral Disorders in Inclusive Placements - Arseneau, Naomi (Journal of the American Academy of Special Education Professionals, 2012)
Over the last several decades, inclusive placements for students with disabilities have become increasingly common. Although benefits are associated with inclusion, questions remain about the effectiveness of these placements for students with Emotional/Behavioral Disorders (E/BD). As a result of the move toward more inclusive placements, the roles of special education teachers are shifting and becoming increasingly complex. As a result, there are a number of important supports that should be provided to teachers of students with E/BD and the students themselves. The purpose of this paper is to examine factors that have an effect on the success of students with E/BD in inclusive placements including the roles of special educators related to collaboration and the critical supports necessary.